The possible role of anoxic alkaline high subcritical water in the construction of the BIFs: the case of the 3.4 Ga Buck Reef Chert, Sth Africa - (:unkn) unknown (My University, 2024)
The Back Reef Chert was emplaced between volcanic events. Two non-homogeneously mixed viscous fluids with high SiO2 content, might have been ejected in flow-banding for the construction of the Banded Iron Formations.
Keywords: African Research